Una revisión al estado del arte de la integración de toma de decisiones en la red logística - Pérez, Cesar Augusto Pineda; López Bello, César Amilcar (Ingeniería, 2013)
This article is the result of the research project entitled “Integration of Decision Making in the logistics network”. It conduct a review of the state of art in which the concept of integration in the supply chain is identifi ed, as well as the types of integration, mechanisms of integration, integration tools, integration strategies and fi nally the benefi ts and performance measures.